Pengaruh Mediasi dari Perceived Responsibilty terhadap Hubungan antara Obedience Pressure dan Budgetary Slack - Sakina Nusarifa Tantri (Sekolah Vokasi Universitas Gadjah Mada, 2018)
This study aims to examine the mediating effect of perceived responsibility on the association between obedience pressure and budgetary slack. The questionnaires were distributed in a survey conducted on 100 participants who are living in Indonesia and involved in the companies budget recommendation. The statistical analysis was performed using SEM. The result of this study showed that obedience pressure has a positive significant effect on budgetary slack and negatively affects perceived responsibility, while perceived responsibility has a negative significant effect on budgetary slack. Further analysis on mediating variable showed that perceived responsibility partially mediated the relationship between obedience pressure and budgetary slack. Keyword: obedience pressure, budgetary slack, perceived responsibility, mediating variable, SEM